2022
DOI: 10.3390/healthcare11010129
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function, Physical Activity, Mean Amplitudes and Maximal Voluntary Contraction of Pelvic Floor Muscles Are Related to Handgrip Strength: A Cross-Sectional Study

Abstract: Pelvic floor musculature assessment methods are generally invasive, subjective, and technologically expensive. Therefore, there is a need to identify other methods that can predict changes in the function of these muscles. This study aimed to verify whether the levels of strength and myoelectric activity of pelvic floor muscles (PFM) can be related to handgrip strength (HGS), to ensure faster and earlier identification of possible dysfunctions of this musculature. Furthermore, we verified whether these variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The measurement of handgrip strength has been reported to be a good indicator of overall muscle strength 10 and can be used as an auxiliary diagnostic tool for PFM disorders. 11 Previous studies have shown an association between handgrip strength weakness and incontinence in older adults. 12 Our study aims to find new cutoff points of handgrip strength as early indicators of incontinence and analyze the association between low handgrip strength and incontinence among Chinese middle‐aged and older people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of handgrip strength has been reported to be a good indicator of overall muscle strength 10 and can be used as an auxiliary diagnostic tool for PFM disorders. 11 Previous studies have shown an association between handgrip strength weakness and incontinence in older adults. 12 Our study aims to find new cutoff points of handgrip strength as early indicators of incontinence and analyze the association between low handgrip strength and incontinence among Chinese middle‐aged and older people.…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to find a simpler, more convenient, and objective indicator to determine the functional level of the PFM. The measurement of handgrip strength has been reported to be a good indicator of overall muscle strength 10 and can be used as an auxiliary diagnostic tool for PFM disorders 11 . Previous studies have shown an association between handgrip strength weakness and incontinence in older adults 12 .…”
Section: Introductionmentioning
confidence: 99%